Olvasás/tér/kép: Az európai festészet hagyománya és a gyerekkönyv-illusztráció - Hermann, Zoltán (Studia Litteraria, 2019)
The illustrated book does not simply attempt to display a particular meaning, but confront the receiver with the temporality and spatiality of reading and visual perception. Starting from the recognition of Derrida, it can be said that we could realise the same spatial structures in the case of written text as in the ones which define the European visual thinking, as the reception and contemplation of a painting is essentially the same as the „economy” of reading: the flat surface always create a fictional one. The good picture and children books are exactly do nothing more, but broadcast the elements of the imaginative thinking of European Civilization and Culture, help to learn and creatively reinterpret this tradition.